Analysis of ore-controlling structures and mineralization prediction of the Guocheng gold deposit in the northeastern margin of the Jiaolai Basin - CAO Peng; YANG Yaqi; ZHENG Chaoyang; WANG Wei; CHEN Yuanlin; LIU Jianzhong; ZHAO Xinghua (Dizhi lixue xuebao)
Objective  The Jiaodong Peninsula is the largest gold metallogenic province in China and represents the third-largest gold enrichment region globally. Most gold deposits in this area formed during the Early Cretaceous and are significantly controlled by NNE–NE trending normal faults. Notably, there are more limited gold reserves from the east of the Jiaodong Peninsula compared with those from the northwestern region. The Guocheng gold deposit with a medium size is located in the northeast of the Jiaolai Basin and develops complex fault structures. These gold ore bodies are mainly hosted within faults but show poor distribution regularity. Thus, it is necessary to determine the ore-controlling structures.   Methods  Through detailed surface and underground geological investigations and structural analysis, this study reveals that ore bodies are primarily controlled by a thrust-faulting system and are mainly hosted within marbles of the Jingshan Group and Muniushan granitic pluton.   Results  Precise structural analysis reveals that the study area had undergone at least three-stage tectonic activities. The first stage (D1) was driven by nearly NW–SE compression and formed NE-trending faults and a series of associated secondary faults. The second stage (D2) involved the NW–SE extension, which developed numerous NE-trending intermediate-basic dike swarms and resulted in the development of the Tudui faults and extensional reactivation of NE-trending faults. During the third stage (D3), the nearly NE-SW compression formed some post-ore-formation structures, including new reverse faults and reactivated pre-existing structures.  Conclusion  This study identifies NE-trending faults as principal ore-controlling structures, and proposes the coupling relationships between ore-bearing faults and the Guocheng and Houkuangdong faults. These main ore-bearing structures belong to the tensional-shear secondary faults in the footwalls of the Guocheng and Houkuangdong faults. The conclusion predicts that there are potential ore bodies in the footwall of the Houkuangdong Fault, which is also further confirmed by the drilling project. [Significance] Although the Guocheng gold deposit was also formed in the Early Cretaceous, the ore-controlling structures in this region are obviously different from the northwestern of the Jiaodong Peninsula, suggesting the heterogeneity of extension deformation in the Jiaodong Peninsula during the mineralization stage. Therefore, the thrust-faulting system may be one of the key ore-controlling structures in the east of the Jiaodong Peninsula.